Menggali Makna Rohani Dalam Kurikulum Pendidikan Agama Kristen - Liena Hulu; Nur Lestari; Sandra Rosiana Tapilaha (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Curriculum is an educational plan that describes all the learning experiences provided to students in an educational institution. This curriculum covers philosophy, values, knowledge and attitudes towards life, and is prepared by academics/curriculum experts, scientists, educators, education officials, entrepreneurs and other members of society. This research method uses a qualitative approach that guides the process of collecting, analyzing and interpreting observations. By using this qualitative research method the author tries to describe the results of the research by collecting data that supports the research using articles and books related to the title exploring spiritual meaning in the Christian Religious Education curriculum. Spiritual meaning in the context of Christian religious education includes understanding and practice which aims to bring students to know and understand God's will, as well as develop their spirituality through contextual and transformative education, by imitating the teachings of Jesus Christ. According to John M. Nainggolan, a Christian Religious Education teacher has several responsibilities which include evaluating the effectiveness of Christian Education in each related educational institution in developing children's spiritual aspects. The educational curriculum, especially in the context of Christian Religious Education, is a comprehensive plan that aims to guide students in acquiring knowledge, attitudes and skills that are in accordance with the values ​​and teachings of the Christian religion.